Ultimate price : the value we place on life - Friedman, Howard Steven, 1972- (University of California Press, 2020)
"Ultimate Price shows a multitude of ways people's lives are being valued, explains the methods involved and then forcefully argues against the rampant unfairness in the system. These price tags on human life often value young lives more than old, rich more than poor, white Americans more than black Americans, Americans more than foreigners and relatives more than strangers. The calculations that underlie these price tags and the dramatic ramifications they have on our lives are often buried in technical language. These price tags are sometimes unfair, yet they influence our economy, our laws and policies. The book explains in simple terms how economists, corporations, regulators, insurance companies make and use these price tags. The limitations in the methods will be spotlighted so readers can understand how these price tags can often be chauvinistic, racist or elitist. Readers will be enlightened, surprised and sometimes angry after learning how these critical calculations work and the issues and implications hidden inside the equations. Regardless of how the price tag is created, the output is a price tag placed on someone's life. This price tag drives decisions that impact nearly all aspects of life, from creating new life to delaying inevitable death. The price tag is reflected in how we spend our time and money. The book shows how these price tags drive political decisions, decisions of criminal punishment and awards in civil suits, decisions ranging from life insurance to healthcare to education investments to abortions"--